Evaluation of the pH of a New Carbonated Soft Drink Beverage: An In Vivo Investigation - David W. Bartlett, BDS, PhD, MRD, FDS, RCS,1 (Journal of Prosthodontics, 2003)
Recently, a modified version of a successful soft drink has been developed that aims to reduce the potential for dental erosion in consumers